2014
DOI: 10.1155/2014/501935
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Material Gradient for Functionally Graded Rectangular Plate with the Finite Element Method

Abstract: The optimum material gradient of a rectangular plate made of functionally graded material (FGM) is determined in this study. Elastic modulus of functionally graded (FG) rectangular plate is assumed to vary continuously throughout the height of the plate, according to the volume fraction of the constituent materials based on the power law, exponential model I, exponential model П, or sigmoid functions. The difference between these distribution functions for the constituents’ volume fraction is discussed in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Different expressions for this distribution shape function can be assumed. Some of the most employed distributions in the literature are power-law functions (P-FGM), exponential functions (E-FGM) and sigmoid functions (S-FGM) [29]. In the present paper, P-FGM is selected.…”
Section: Functionally Graded Cntrc Platesmentioning
confidence: 99%
“…Different expressions for this distribution shape function can be assumed. Some of the most employed distributions in the literature are power-law functions (P-FGM), exponential functions (E-FGM) and sigmoid functions (S-FGM) [29]. In the present paper, P-FGM is selected.…”
Section: Functionally Graded Cntrc Platesmentioning
confidence: 99%
“…Helal and Shi [8] discussed the difference between the distribution functions for the constituents'volume fraction, and the results outcomes from their investigation have indicated that, the optimum material gradient for FGMs can be described by using a modified sigmoid function. Thus, in the current study, the elastic modulus (E) of FGEPP will be assumed to vary continuously throughout the height of the EPP, according the volume fraction of the constituent materials based on the sigmoid function.…”
Section: Introductionmentioning
confidence: 99%
“…Wasim and Dong [9] discussed the difference between the distribution functions for the constituents'volume fraction, and the results have indicated that, the optimum material gradient for FGMs can be described by using a modified sigmoid function. Thus, in this paper, E of FGEPPP will be assumed to vary continuously throughout the height of the EPPP, according the volume fraction of the constituent materials based on the sigmoid function.…”
Section: Introductionmentioning
confidence: 99%